Maternal Characteristics And Health Promotion Strategies Influencing Pregnant Women’s Perceptions of Stunting Prevention - Eko Mindarsih; Dewi Setyaningsih; Suwarsi Suwarsi; Arita Murwani; Retna Tri Astuti (STIKES Mamba'ul 'Ulum Surakarta, 2026)
Background: Stunting is a health problem that is still a concern in Indonesia. Factors that can influence the occurrence of stunting in toddlers include age, income, gravida, and health promotion strategies. Objective: This study contributes to analyzing factors such as age, income, gravida, and health promotion strategies on maternal perceptions of stunting prevention. Method: Survey with a cross-sectional approach. The study population was pregnant women living in Kulon Progo Regency, Indonesia. The study sample was 210 pregnant women. Data were collected using a questionnaire. Data analysis was performed using the Chi-Square statistical test. Results: The study showed that the majority of pregnant women's perceptions were in the Inadequate category (52.9%). Occurred at a non-risk age (85.7%), low socioeconomic (71%), and the majority of multigravida (55.7%), Health promotion strategies were in the good category (53.8%). Maternal characteristics such as age, income, and gravida showed no significant association with perceptions of stunting prevention, whereas adequate exposure to health promotion strategies was strongly associated with better perceptions with a P Value of 0.000. Conclusion: Adequate exposure to health promotion strategies is positively associated with pregnant women's perceptions of stunting prevention, while maternal characteristics such as age, income, and gravida do not show a significant relationship.